Phosphorus sorption characteristics of some representative soils of south India (SAARC Journal of Agriculture, 2015)
Studies were conducted to investigate P sorption characteristics of representative soils from ten locations of alfisol and ultisol of India using Langmuir and Freundlich equations. The P sorption maxima (b) of soils derived from Langmuir equation in alfisol varied from 520.6 to 574.7 ?g g-1 and ultisol varied from 561.6 to 678.1 ?g g-1. The maximum phosphorus buffering capacity (MPBC) in alfisol ranged from 80.7 to 180.2 ml ?g-1 and ultisol ranged from 162.1 to 284.4 ml ?g-1. Phosphorus sorption maxima was significantly correlated with clay (r2=0.70), Al (r2= 0.73) and Fe (r2=0.81) forms, MPBC (r2=0.67) and Freundlich constants (r2=0.82). The standard P requirement (SPR) to maintain 0.2 mg l-1 P in soil solution for alfisol ranged from 15.62 to 27.62 mg kg-1 and ultisol from 41.98 to 46.35 mg kg-1. The SPR (0.2 mg l-1) was significantly correlated with binding strength coefficient (r2= 0.97) and binding strength coefficient supporting the fact that energy coefficient of a soil is an important index for planning P management strategies. Among the two soil orders in order to maintain optimum P concentration in soil solution for crop growth, ultisol will be required to supply with more P fertilizer as compared to alfisol.SAARC J. Agri., 13(1): 14-26 (2015)